DIETA DE PEIXES TELÓSTEOS DO PANTANAL SUL-MATOGROSSENSE - LOPES, Douglas Alves; VIEIRA, Kelly Regina Ibarrola; COSTA, Fábio Edir dos Santos; MOTA, Rafael da Silva; SOUZA, Mateus rojas Franco de (ANAIS DO ENIC, 2017)
-